2021
DOI: 10.35445/alishlah.v13i2.956
|View full text |Cite
|
Sign up to set email alerts
|

Teaching English Grammar in an Indonesian Junior High School

Abstract: English grammar has a pivotal position in language learning. It is also considered the basis of a series of language skills (listening, speaking, reading, and writing). However, although previous studies focused on teaching English grammar either from a traditional or functional view, where English as L1 and L2 across various educational levels, scarce studies have emphasized teaching English Grammar in the Indonesian EFL context, particularly in Junior High School. Hence, this study aimed at filling such a vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 13 publications
0
14
0
1
Order By: Relevance
“…The status of English as a foreign language in Indonesia affects the English language skills of Indonesian students. In particular, the ability of junior high school students was quite lacking, for example in learning grammar (Andriani, Yuniar, & Abdullah, 2021). Septianasari et al (2019) found that Indonesian students' English proficiency is closely related to the influence of their mother tongue, which affects students' pronunciation and syntax.…”
Section: Discussionmentioning
confidence: 99%
“…The status of English as a foreign language in Indonesia affects the English language skills of Indonesian students. In particular, the ability of junior high school students was quite lacking, for example in learning grammar (Andriani, Yuniar, & Abdullah, 2021). Septianasari et al (2019) found that Indonesian students' English proficiency is closely related to the influence of their mother tongue, which affects students' pronunciation and syntax.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, grammar is no longer become the focus for teaching EFL in schools and university (Toprak, 2019). Some universities immersed the grammar course into English skills courses (Hanganu, 2015) and not many schools in Indonesia provide specific class for teaching grammar (Andriani et al, 2021). So, there was no specific English grammar course anymore.…”
Section: Grammarmentioning
confidence: 99%
“…Menurut Mahdi (2018), struktur atau gramatika Bahasa Inggris masih menjadi persoalan yang kompleks. Andriani et al (2021) juga sependapat bahwa struktur/gramatika bahasa Inggris memiliki posisi penting dalam pembelajaran bahasa. Area ini dianggap sebagai dasar dari rangkaian keterampilan lain dalam berbahasa yaitu menyimak, berbicara, membaca, dan menulis.…”
Section: Pendahuluanunclassified